Assessment and Investigation of Sugar Cane Bagasse Ash as a Binding Material for the Construction Industry - E. Basika; J. Kigozi; N. Kiggundu (Modern Advances in Geography, Environment and Earth Sciences Vol. 3, 2021)
Sugarcane bagasse ash (SCBA) is a by-product of the sugar factories produced after burning sugarcane bagasse in the production of electricity. The sugarcane bagasse is produced after the extraction of all economical sugar from sugarcane. The disposal of this material is a common environmental problem in factories producing electricity from sugarcane. In Kakira Sugar Limited (KSL) about 61,000 tons / yr. of SCBA is produced and only about 30,000 tons / yr of this is utilized, and the remaining is damped which becomes an environmental hazard. This research was, conducted to examine the potential of bagasse ash as a cement replacing material in construction industry. The idea of using SCBA as a building material has generated additional cash flow for the sugarcane processing mills. Bagasse ash samples were collected from KSL and its chemical properties were investigated. The compressive strength of mortars containing ordinary Portland cement and SCBA in proportions of 0%, 10%, 15%, 20%, 25%, 30% and 40% as a cement replacement were investigated. Three replicates with the bagasse ash replacing ordinary Portland cement in the above mentioned proportions were prepared and tested. The results showed that ordinary Portland cement can be replaced by SCBA up to 20% without affecting the compressive strength of the mortar at a test age of 28 days. These findings suggest that replacement of cement with SCBA could results in the reduction in cost of construction. Hence it can be concluded that it is safe to replace cement with sugar cane bagasse ash up to 20%.